2014
DOI: 10.1016/j.carbon.2014.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Graphene grown on Ge(0 0 1) from atomic source

Abstract: Among the many anticipated applications of graphene, some -such as transistors for Si microelectronics -would greatly benefit from the possibility to deposit graphene directly on a semiconductor grown on a Si wafer. We report that Ge(001) layers on Si(001) wafers can be uniformly covered with graphene at temperatures between 800 • C and the melting temperature of Ge. The graphene is closed, with sheet resistivity strongly decreasing with growth temperature, weakly decreasing with the amount of deposited C, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 73 publications
0
67
0
1
Order By: Relevance
“…However, graphene transfer from Ge substrate to desired substrates led to wrinkled and folded regions. Lippert et al have also reported direct uniform deposition of graphene on Ge (001) layers on Si (001) wafers. Their results indicate that graphene can be directly deposited at the active regions of Si transistors with a process compatible with Si technology.…”
Section: Cvd Growth Of Graphenementioning
confidence: 99%
“…However, graphene transfer from Ge substrate to desired substrates led to wrinkled and folded regions. Lippert et al have also reported direct uniform deposition of graphene on Ge (001) layers on Si (001) wafers. Their results indicate that graphene can be directly deposited at the active regions of Si transistors with a process compatible with Si technology.…”
Section: Cvd Growth Of Graphenementioning
confidence: 99%
“…For example, implementation of graphene in the present-day scalable semiconducting technology requires its synthesis on insulating or semiconducting substrates. Presently this is only possible on h-BN [7][8][9][10] and Ge [11][12][13][14][15] substrates at the conditions which cannot be easily adapted.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently, germanium, a group IV semiconductor, has emerged as a viable substrate for graphene epitaxy. [7][8][9] High quality epitaxial growth on semiconductor wafers is very attractive because it presents a path toward production by existing very large scale integration processes. Graphene growth on Ge(110) by chemical vapor deposition (CVD) has been shown to exhibit considerably improved rotational alignment compared with growth on Ge(111).…”
Section: Introductionmentioning
confidence: 99%